Model Flipped Classroom Melalui Strategi Literasi Pra-Kelas untuk Meningkatkan Pemahaman dan Keterampilan Berpikir Kreatif Mahasiswa - Sari, Indah; Khoirunnida, Nabhan Robbany (Al-Qalam: Jurnal Kajian Islam dan Pendidikan, 2025)
This study aims to improve students' creative thinking skills through the implementation of the Flipped Classroom model combined with a pre-class literacy strategy. Pre-class literacy activities are designed to provide students with initial knowledge before the lecture, so that they are better prepared for learning and can increase active participation in class discussions. The sample consisted of 75 students of 4th semester Islamic Education Study Program students, who were selected through purposive sampling. Data were collected through a Likert scale-based questionnaire and analyzed using descriptive statistical methods. The results showed that pre-class literacy activities had a significant impact on various aspects of students' abilities. Most respondents felt that literacy improved their understanding of the material (mean = 4.58) and their readiness to attend lectures (mean = 4.48). In addition, literacy activities also improved students' creative thinking skills, with 36% of respondents strongly agreeing that literacy contributed to the improvement of creative thinking skills. This finding is in line with previous research that revealed a positive relationship between literacy and creative thinking skills. Overall, this study shows that the implementation of the Flipped Classroom model combined with pre-class literacy strategies can improve students' material understanding, learning readiness, and creative thinking skills.